2010
DOI: 10.1159/000320776
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Model of Severe Gallstone Pancreatitis: Murine Pancreatic Duct Ligation Results in Systemic Inflammation and Substantial Mortality

Abstract: Background: Suitable experimental models of gallstone pancreatitis with systemic inflammation and mortality are limited. We developed a novel murine model of duct-ligation-induced acute pancreatitis associated with multiorgan dysfunction and severe mortality. Methods: Laparotomy was done on C57/BL6 mice followed by pancreatic duct (PD) ligation, bile duct (BD) ligation without PD ligation, or sham operation. Results: Only mice with PD ligation developed acute pancreatitis and had 100% mortality. Pulmonary comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 19 publications
4
30
0
Order By: Relevance
“…Midline laparotomy was performed on mice under general anesthesia with isoflurane. 1 Postoperatively, mice were allowed access to food and water ad libitum and were given buprenorphine analgesia and 1 cm 3 sterile normal saline s.c. hydration twice daily. The mice were monitored for physical activity, grooming, alertness, response to stimulation, and other signs of stress at least two times daily.…”
Section: Animal Surgerymentioning
confidence: 99%
See 4 more Smart Citations
“…Midline laparotomy was performed on mice under general anesthesia with isoflurane. 1 Postoperatively, mice were allowed access to food and water ad libitum and were given buprenorphine analgesia and 1 cm 3 sterile normal saline s.c. hydration twice daily. The mice were monitored for physical activity, grooming, alertness, response to stimulation, and other signs of stress at least two times daily.…”
Section: Animal Surgerymentioning
confidence: 99%
“…The mice were studied in three experimental groups: (1) sham operation (S): the distal bile-pancreatic duct was dissected but not ligated, (2) bile duct ligation (BD): only the common bile duct was ligated prior to its junction with the splenic portion of the pancreatic duct, and (3) distal common bile-pancreatic duct ligation (PD): the common bile-pancreatic duct was ligated near its junction with the duodenum. In our previous study, 1 we have already shown that acute pancreatitis induced by PD alone results in similar mortality and morphological pancreatic changes as PD+BD, and therefore we limited our studies to PD in the present study. It must be noted that PD will cause biliary obstruction in addition to obstructing outflow from the pancreatic ductal system and that BD alone for 2 weeks is not associated with mortality in our model.…”
Section: Animal Surgerymentioning
confidence: 99%
See 3 more Smart Citations